In-phase anomalies in Beryllium-10 production and palaeomagnetic field behaviour during the Iceland Basin geomagnetic excursion - Knudsen, M; Henderson, G; Frank, M; Mac Niocaill, C; Kubik, P (2008)
Increases in the production rate of cosmogenic radionuclides associated with geomagnetic excursions have been used as global tie-points for correlation between records of past climate from marine and terrestrial archives. We have investigated the relative timing of variations in 10Be production rate and the corresponding palaeomagnetic signal during one of the largest Pleistocene excursions, the Iceland Basin (IB) event (ca. 190 kyr), as recorded in two marine sediment cores (ODP Sites 1063 and 983) with high sedimentation rates. Variations in 10Be production rate during the excursion were estimated by use of 230Thxs normalized 10Be deposition rates and authigenic 10Be/9Be. Resulting 10Be production rates are compared with high-resolution records of geomagnetic field behaviour acquired from the same discrete samples. We find no evidence for a significant lock-in depth of the palaeomagnetic signal in these high sedimentation-rate cores. Apparent lock-in depths in other cores may sometimes be the result of lower sample resolution. Our results also indicate that the period of increased 10Be production during the IB excursion lasted longer and, most likely, started earlier than the corresponding palaeomagnetic anomaly, in accordance with previous observations that polarity transitions occur after periods of reduced geomagnetic field intensity prior to the transition. The lack of evidence in this study for a significant palaeomagnetic lock-in depth suggests that there is no systematic offset between the 10Be signal and palaeomagnetic anomalies associated with excursions and reversals, with significance for the global correlation of climate records from different archives. © 2007 Elsevier B.V. All rights reserved.